Estimación de reservas en una compa\~nía aseguradora: Una aplicación en Excel del método Chain-Ladder y Bootstrap - José Antonio Álvarez-Jare\~no; Vicente Coll-Serrano (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2012)
– Insurance companies have to estimate reserves and provisions to cover the payment of either unreported claims or unsettled claims. In this paper, we apply the Chain-Ladder method to obtain a point estimate of reserves, and then we use the bootstrap technique to estimate the margin of error and the confidence interval of the reserves. Since estimating reserves is a real problem which insurance companies have to face, its solving has a special interest for students of Actuarial Sciences. To ease the understanding and monitoring the process, the Chain-Ladder method and bootstrap is run step by step by using an Excel application designed for that purpose.
Keywords: G22; C12; C63; 330; bootstrap; Chain-Ladder method; reserves; insurance company; Excel